Comparison of the effects of simulation training and problem-based scenarios on the improvement of graduating nursing students to speak up about medication errors: A quasi-experimental study. (April 2020) - Kuo, Shu-Yu; Wu, Jen-Chieh; Chen, Hui-Wen; Chen, Chia-Jung; Hu, Sophia H.
Abstract: Background: Medication administration errors are common among new nurses. Nursing students might be less willing to speak up about errors because of a lack of knowledge and experience. Objectives: To examine the effects of simulation training and problem-based scenarios on speaking up about medication errors among graduating nursing students. Design: Prospective, controlled experimental study design. Setting: A university four-year nursing program in Taiwan. Participants: In total, 93 graduating nursing students in their last semester were recruited. Sixty-six students who received both a problem-based scenario and medication administration simulation training comprised the experimental group, while 27 students who received problem-based scenarios alone comprised the control group. Methods: Experimental group students underwent 2 h of simulation training. This training class was designed based on Kolb's experiential learning theory for knowledge development and speaking up about errors. Students in both groups administered medications in problem-based scenarios with eight embedded errors. Students' performance in speaking up about medication errors was directly observed and graded using an objective structured checklist. The McNeamer Chi-squared test, paired t -test, Z test, t -test, and Hedges' g effect size were conducted. Results: The number of times participants spoke up about medication errors significantly improved in both the experimental group (pre-test: 2.05 ± 1.12 and post-test 6.14 ± 1.25, t = 22.85, p <0.001) and control group (pretest: 2.04 ± 1.16 and post-test: 4.26 ± 1.63, t = 6.33, p <0.001). However, after the intervention, the mean number of times participants spoke up about medication errors in the experimental group was significantly higher than that in the control group ( t = 5.99, p <0.001) in the post-test. Conclusions: Simulation training exhibited more-significant improvements than problem-based scenarios. Nursing schools and hospitals should incorporate simulation training or at least problem-based scenarios to improve medication safety.